EFFECT OF MERCURIC CHLORIDE ON THE OVARY OF FRESHWATER CRAB BARYTELPHUSA CUNICULRIS - F. I. SHAIKH; N. T. ANSARI (The Bioscan, 2010)
The effect of mercuric chloride on the histopathalogy of ovary showed pycnosis of nutritive cells and shrinkage of ooctye. Destruction of epithelial layer and degeneration of oocyteswas foundThe epidermal layer was loosely arranged. Vacuolization was also observed in the periphery of the oocyte cells during acute and chronic treatment.